Catalysts for Production of Biofuels from Palm Oil-based Feedstock in Jambi Province: A Review of Performance and Potential - Pratama, Seftiananda; Nazarudin, Nazarudin (PUI BiGME Universitas Jambi, 2022)
Palm oil is a crucial agricultural commodity in Jambi Province. It holds significant promise for biofuel production, but the use of catalysts is essential for improving the process's efficiency. This study extensively assesses various catalysts' performance and potential in the context of biofuel production from palm oil-based feedstock in Jambi Province. It examines different catalysts, evaluating their effectiveness in terms of yield, selectivity, while also addressing challenges/opportunities for their development and commercialization in the region. The review of existing research underscores the diversity of catalysts explored for palm oil-based biofuel production in Jambi Province. The findings emphasize that catalysts can substantially enhance both yield and selectivity in the biofuel production process. However, there's a pressing need for further research to create more efficient and cost-effective catalysts for sustainable biofuel production. This research aims to identify catalyst types investigated for biofuel production from palm oil-based feedstock in Jambi Province, assess their performance and potential and offer a comprehensive overview of catalyst development in this context. The study's prospective contribution is as a valuable resource for researchers and developers, aiding future research and development efforts and accelerating the commercialization of improved catalysts for sustainable biofuel production in Jambi Province